Impact of Gravity Model and Domestic Market Obligation (DMO) on Coal Indonesian Export - Nurul Azizah Az-zakiyah (Optimum: Jurnal Ekonomi dan Pembangunan, 2023)
This study aims to determine the effect of Indonesia's GDP per capita, GDP per capita destination country, real exchange rate, the population of the destination country, the distance between Indonesia and the country's objectives, and the variable of the Domestic Market Obligation (DMO) dummy for Indonesia's coal exports by using the gravity model. This study uses panel model regression with a research period of 2012-2022. The study results show that Indonesia's GDP per capita variable significantly negatively affects exports of Indonesian coal. GDP per capita of the destination country, the population of the destination country, the real exchange rate, and dummy DMO significantly positively affect Indonesia's coal exports. Whereas distance has no significant impact on Indonesia's coal exports